A melamine formaldehyde product and preparation method thereof
By setting up the performance improvement layer of polyamide resin and glass fiber on the level of desertide formaldehyde, the problem of insufficient toughness and poor high temperature resistance of mighty products and high temperature, high safety and high temperature -resistant desertide products are solved. Essence
Patent Information
- Application Number
- CN202410593688.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-14
AI Technical Summary
Existing melamine products have problems such as insufficient toughness, poor high temperature resistance and residual formaldehyde and melamine monomers, which lead to prone to rupture and precipitation of harmful substances during transportation, use and high temperature disinfection.
By setting a performance-enhancing layer containing polyamide resin and glass fiber on at least one side of the melamine formaldehyde base layer, combined with reasonable layer design and component design, the problem of difficult mixing is solved, and the toughness and toughness of melamine products are improved. High temperature resistance.
It significantly improves the toughness and high-temperature resistance of melamine products, reduces the migration of formaldehyde and melamine, complies with national food safety standards, and is suitable for tableware, sanitary ware, electrical home decoration and other fields.
Smart Images

Figure CN118496665B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material processing technology, specifically relating to a melamine formaldehyde product and its preparation method. Background Technology
[0002] Melamine-formaldehyde resin (referred to as melamine resin) is mainly composed of melamine and formaldehyde. After curing, it has a three-dimensional network cross-linked structure. Molding plastics (referred to as melamine molding plastics) made with melamine resin as the base material and other additives are widely used in the production of tableware, electrical components, and household goods due to their advantages such as being lightweight, beautiful, and impact-resistant.
[0003] Melamine products currently have the following problems:
[0004] First, melamine resin has a high degree of crosslinking during the crosslinking process, making it very brittle and prone to cracking. As a result, current melamine products still lack toughness and are prone to breakage during transportation and use.
[0005] Second, the residue of small molecules such as formaldehyde and melamine monomers when melamine materials are used to make tableware is also a difficult problem to solve. At the same time, melamine products have poor high temperature resistance, which makes it easy for small molecules to be released when used or disinfected at high temperatures, posing a certain risk to the human body. Its use temperature generally cannot exceed 120℃, which seriously limits the application range of melamine products.
[0006] Patent document with application number 201710249103.5 discloses a method for preparing antibacterial and wear-resistant melamineware, including the following steps: preparing a KH-550 aqueous solution with a mass fraction of 1-2%, then adding zinc oxide whisker functional powder, and then spraying the mixture onto pulp and mixing evenly to obtain antibacterial pulp; putting melamine-formaldehyde resin into a kneader, adding antibacterial pulp and kneading to obtain slurry; then putting the slurry into a dryer for drying, grinding, and sieving to obtain antibacterial and wear-resistant melamine raw material; taking a certain amount of antibacterial and wear-resistant melamine raw material, preheating it to 40-50℃, then putting it into a preheated mold, applying pressure to cause the antibacterial and wear-resistant melamine raw material to undergo a condensation reaction and generate gas, venting the gas, applying pressure again to cure, opening the mold, and polishing.
[0007] The aforementioned prior art involves adding zinc oxide whiskers to paper pulp to prepare antibacterial pulp, and then mixing the antibacterial pulp into melamine resin to give the resulting tableware long-lasting antibacterial properties. It can also decompose free organic matter such as formaldehyde in melamine tableware and improve the wear resistance of melamine tableware. However, this prior art mainly focuses on improving the antibacterial properties of melamine products, while its melamine products still have problems with poor toughness and high temperature resistance.
[0008] In summary, the present invention aims to provide a melamine product with high toughness, high safety and high temperature resistance. Summary of the Invention
[0009] In response to the problems in related technologies, this invention proposes a melamine-formaldehyde product and its preparation method to solve the problems of monomer residue, release of harmful substances, poor high-temperature thermal stability, and insufficient toughness that lead to poor drop resistance in existing melamine plastic tableware.
[0010] The technical solution of this invention is implemented as follows:
[0011] A melamine-formaldehyde product includes at least one melamine-formaldehyde base layer, wherein the melamine-formaldehyde base layer has a performance enhancement layer on at least one side.
[0012] The raw material for preparing the performance enhancement layer is designated as material A, which contains the following parts by weight: 100 parts of polyamide resin (PA) and 5-35 parts of glass fiber.
[0013] The raw material for preparing the melamine-formaldehyde base layer is designated as material B, which contains the following parts by weight: 100 parts of base material, 5-50 parts of filler, 0.01-1 parts of antioxidant, 0.01-1 parts of curing agent, and 0.01-1 parts of release agent.
[0014] The base material comprises pulp, one of plant fibers, and melamine resin in a weight ratio of 1 to 4:10.
[0015] Preferably, the melamine-formaldehyde product per unit area comprises 50-90 wt% of material B and 10-50 wt% of material A.
[0016] Preferably, the polyamide resin is one or a mixture of two of PA6 and PA66 in any proportion.
[0017] Preferably, the particle size of the polyamide resin is ≤0.28mm.
[0018] Specifically, the polyamide resin is obtained by grinding polyamide resin granules. The specific operation is as follows: coarse particles in the polyamide resin granules are screened out using a sieve with a mesh size of ≥50 mesh and then ground. The grinding temperature is -50 to 0℃ and the grinding time is 0.5 to 6 hours. The granules are then sieved again using a sieve with a mesh size of ≥50 mesh to obtain polyamide resin with a particle size of ≤0.28mm.
[0019] The glass fiber is a short chopped glass fiber with a length of 1.5 to 15 mm, preferably 3 to 12 mm, and more preferably 5 mm.
[0020] The glass fiber is a glass fiber modified with a coupling agent.
[0021] Preferably, the coupling agent is one or more of silane coupling agents, aluminate coupling agents, and titanate coupling agents in any proportion; more preferably, the coupling agent is silane coupling agent KH550.
[0022] Preferably, material A may further include a colorant and a lubricant, wherein the colorant has a weight of ≤5 parts and the lubricant has a weight of ≤2 parts.
[0023] The lubricant is one or more of zinc stearate, magnesium stearate, ethylene bis-stearamide, calcium stearate, dimethyl silicone oil, and methyl phenyl silicone oil in any proportion; zinc stearate is preferred as the lubricant.
[0024] The colorant is one or more of titanium dioxide, lithopone, iron oxide red, iron oxide yellow, carbon black, ultramarine, phthalocyanine blue, aluminum powder, and fluorescent whitening agent; the titanium dioxide is preferably rutile type (R type).
[0025] Preferably, the melamine resin has a molecular weight of 300-1000, is in a dry state, and has a water content of ≤2%; more preferably, the melamine resin has a water content of ≤1.5%.
[0026] Preferably, the fiber is one or more of wood fiber, bamboo fiber, hemp fiber, rice straw fiber, and cellulose in any proportion.
[0027] More preferably, the cellulose is α-lignocellulose, and can be one or a mixture of two of the following in any proportion: α-lignocellulose from broadleaf wood and α-lignocellulose from coniferous wood.
[0028] Preferably, the melamine resin and cellulose are kneaded to form the base material, the kneading comprising the following steps:
[0029] 1) Mix melamine resin and cellulose in a kneader according to the weight ratio until homogeneous. Set the temperature of the kneader to ≤80℃ and the kneading time to 30-60 minutes.
[0030] 2) Place the kneaded material from step 1) in hot air at 80-90℃ and dry it evenly. After dehydration and drying, the base material is obtained.
[0031] Preferably, the filler is one or more of the following in any proportion: talc powder, heavy calcium carbonate, light calcium carbonate, kaolin, mica powder, dolomite, barium sulfate, graphene oxide, maifanite powder, silicon powder, alumina, montmorillonite powder, diatomaceous earth, and mineral fibers.
[0032] Preferably, the particle size of the filler is ≤0.025mm, and more preferably ≤0.013mm.
[0033] More preferably, the filler is light calcium carbonate with a whiteness ≥90 and an average particle size ≤0.013mm.
[0034] Preferably, the filler is a filler that has undergone activation treatment through the following steps:
[0035] 1) Weigh out the surface modifier, wherein the amount of the surface modifier is 0.1 to 1 wt% of the filler;
[0036] The surface modifier is one or more of silane coupling agents, titanate coupling agents, and aluminate coupling agents in any proportion; the preferred surface modifier is silane coupling agent KH550.
[0037] 2) Using anhydrous ethanol as a solvent, prepare a surface modifier solution with a concentration of 10-30 wt%.
[0038] 3) Set the temperature of the mixing equipment to 80-100℃, place the filler in the mixing equipment and rotate it at a speed of 1000-1500 r / min. At the same time, spray the modifier solution prepared in step 2) onto the filler and stir for 15-30 min.
[0039] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 3114, and antioxidant 168 in any proportion;
[0040] More preferably, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1.
[0041] The curing agent is one or more of phthalic anhydride, methylhexahydrophthalic anhydride, aminosulfonic acid amine, and acetyldiphenylamine in any proportion; preferably, the curing agent is phthalic anhydride.
[0042] The release agent is one or more of zinc stearate, magnesium stearate, ethylene bis-stearamide, calcium stearate, dimethyl silicone oil, and methylphenyl silicone oil in any proportion; zinc stearate is preferred as the release agent.
[0043] Preferably, the particle size of material B is 0.16 to 0.35 mm; more preferably, the average particle size of material B is 0.19 mm.
[0044] Specifically, the material B is pre-treated before grinding. The specific operation is as follows: material B is put into a ball mill and ground for 3 to 24 hours at a cylinder speed of 15 to 40 r / min. The temperature of material B is kept ≤50℃ during the grinding process. The material B is sieved through a screen with a mesh size ≥40 to obtain material B with a particle size ≤0.35mm.
[0045] In actual production, material B can also be mixed with appropriate amounts of color powder and other additives as needed.
[0046] The present invention also discloses another technical solution, wherein the melamine formaldehyde product may further include at least one photosensitive layer, wherein the photosensitive layer is the outermost layer on any side of the melamine formaldehyde product.
[0047] The raw material for preparing the light powder layer is material C. The melamine formaldehyde product per unit area contains ≤5wt% of material C. Material C is melamine powder with a purity of ≥99%. The melamine powder can improve the surface gloss and hardness of the melamine product of the present invention.
[0048] Preferably, the melamine formaldehyde product may further include at least one decorative layer formed of decorative decals.
[0049] The method for preparing the decorative decal is as follows: melamine powder is added to water at 60-100°C and stirred evenly to prepare a mixture containing 40-80 wt% melamine powder; the mixture is then coated onto the surface of the decal with a coating thickness of 0.05-0.2 mm and dried to obtain the decorative decal.
[0050] Preferably, the particle size of the melamine photosensitive agent is 0.16 to 0.35 mm.
[0051] The decorative paper can be patterned paper, and it should be noted that the decorative paper meets the requirements for making the corresponding melamine products. For example, if the melamine product is tableware, then the decorative paper needs to meet the standard requirements for making melamine tableware.
[0052] This invention also discloses a method for preparing the above-mentioned melamine-formaldehyde product, comprising the following steps:
[0053] 1) Prepare material A, and mold material A. The mold temperature is 200-270℃, the molding pressure is 10-30MPa, the molding time is 40-90s, and the venting is done once in the middle, with a venting time of 1-3s.
[0054] After molding is completed, the mold is cooled to 160-190℃ to obtain the performance enhancement layer;
[0055] 2) Configure the material B, stack the material B on at least one side of the performance enhancement layer, and perform molding together. The mold temperature is 150-190℃, the molding pressure is 10-30MPa, the molding time is 40-90s, and the venting is done once in the middle, with a venting time of 1-3s.
[0056] After molding, a composite melamine-formaldehyde base layer and a performance-enhancing layer are formed. The mold is cooled to ≤140℃, demolded, trimmed, and polished to obtain melamine-formaldehyde products.
[0057] If the melamine formaldehyde product produced has a luminous powder layer and / or a decorative layer, then after molding is completed in step 2), a material C that can form a luminous powder layer and / or decorative decals are laid on at least one side of the melamine formaldehyde base layer and / or performance enhancement layer, and hot pressing is performed. The hot pressing temperature is 150-190°C, the hot pressing time is 5-10s, and the hot pressing pressure is 12-18MPa.
[0058] Preferably, in step 2), the material B is preheated before being added to the mold.
[0059] The specific operation of the preheating treatment is as follows: the material B is placed in a high-frequency (high-frequency) preheater, the preheating temperature is 80-140℃, and the preheating time is 20-60s. This softens and heats the material B, and the high-frequency electromagnetic field causes the internal molecules of the material B to vibrate and generate heat energy, thereby maturing the material B into a clump-like gel, which is convenient for processing.
[0060] The beneficial effects of this invention are:
[0061] Most existing technologies directly add toughening components to melamine resin for mixing, but this results in difficulties in dispersing and mixing the materials, thus affecting the performance improvement effect. This invention solves this problem through reasonable layer and component design. A performance-enhancing layer containing polyamide and glass fiber is provided on at least one side of the melamine-formaldehyde base layer, which not only solves the mixing difficulty problem, but also significantly improves the toughness and high-temperature resistance of the melamine products of this invention. At the same time, the melamine products obtained by this invention have extremely low formaldehyde and melamine migration, which meets the national food safety standard "General Safety Requirements for Food Contact Materials and Articles", and are environmentally friendly, and can be applied to tableware, bathroom fixtures, home appliances and other fields. Attached Figure Description
[0062] Figure 1 These are schematic diagrams of the structures of Embodiments 1 and 2 of the present invention;
[0063] Figure 2 This is a schematic diagram of the structure of Embodiment 3 of the present invention;
[0064] Figure 3 This is a schematic diagram of the structure of Embodiment 4 of the present invention.
[0065] Figure Labels
[0066] 1. Performance enhancement layer; 2. Melamine formaldehyde base layer; 3. Gloss powder layer; 4. Decorative layer. Detailed Implementation
[0067] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0068] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," and "counterclockwise," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0069] Example 1
[0070] Prepare raw materials
[0071] A. Prepare the raw materials for forming the performance enhancement layer, denoted as material A.
[0072] Material A comprises the following raw materials by weight:
[0073] 100 kg of polyamide resin (PA66), particle size ≤ 0.28 mm;
[0074] 15 kg of glass fiber treated with (aluminate coupling agent ASA), wherein the glass fiber is 5 mm long chopped glass fiber.
[0075] A-1) The polyamide resin is obtained by grinding polyamide resin granules.
[0076] The specific grinding operation is as follows: use a 50-mesh sieve to screen out the coarse particles in the polyamide resin granules and grind them. The grinding temperature is -10℃ and the grinding time is 2 hours. Then, use a 50-mesh sieve again to sieve to obtain polyamide resin with a particle size ≤0.28mm, and then package and store it.
[0077] B. Prepare the raw materials for forming the melamine-formaldehyde base layer, denoted as material B.
[0078] Material B comprises the following raw materials by weight:
[0079] 100 kg of base material, wherein the base material comprises melamine resin (number average molecular weight of 421, dry state, moisture content ≤2%) and wood fiber in a weight ratio of 10:1.5;
[0080] The filler is composed of 4 kg of heavy calcium carbonate and 6 kg of diatomaceous earth, with a particle size ≤ 0.25 × 10⁻⁶. -3 mm;
[0081] Antioxidant (antioxidant 3114) 0.01 kg;
[0082] Curing agent (methylhexahydrophthalic anhydride) 0.02 kg;
[0083] Release agent (dimethyl silicone oil) 0.01 kg.
[0084] B-1) The melamine resin and fiber are first kneaded to form the base material.
[0085] The specific kneading operation is as follows: melamine resin and fiber are mixed evenly in a kneader according to the weight ratio. The kneader is set to a temperature of 80°C and the kneading time is 30 minutes. After kneading, the material is placed in 80°C hot air for even drying. After dehydration and drying, the base material is obtained.
[0086] B-2) Pre-grinding treatment of material B:
[0087] The specific operation is as follows: put material B into a ball mill and grind for 4 hours. The cylinder speed is 15 r / min. The ball mill jacket must be cooled by cooling water. During the grinding process, the temperature of material B should be kept ≤50℃. The material B is then sieved through a 40-mesh sieve to obtain material B with a particle size ≤0.35mm, and then packaged and stored.
[0088] C. The preparation method of melamine formaldehyde products includes the following steps:
[0089] 1) Material B is preheated. Specifically, material B is placed in a high-frequency (high-frequency) preheater at a preheating temperature of 140°C for 20 seconds.
[0090] 2) Prepare and mix the material A. The mixed material A is molded in the female mold and the first male mold of the two-color molding press. The melamine formaldehyde product per unit area contains 20wt% material A. The mold temperature is 200℃, the molding pressure is 15MPa, the molding time is 45s, and there is one venting in the middle with a venting time of 1s.
[0091] After molding, the mold temperature is reduced to ≤180℃ to obtain the performance enhancement layer;
[0092] 3) Open the first male mold, and stack material B on the upper surface of the formed performance enhancement layer. The melamine formaldehyde product per unit area contains 80wt% of the material B. Combine the second male mold for compression molding. The mold temperature is 160℃, the compression pressure is 20MPa, the compression time is 50s, and the venting is done once in the middle for 2s.
[0093] After molding, a composite melamine-formaldehyde base layer and a performance-enhancing layer are formed. The mold is cooled to ≤140℃, demolded, trimmed, and polished to obtain melamine-formaldehyde products.
[0094] like Figure 1 As shown, the melamine product prepared in this embodiment has a melamine-formaldehyde base layer 2, and a performance enhancement layer 1 is provided on one side of the melamine-formaldehyde base layer 2.
[0095] Example 2
[0096] Prepare raw materials
[0097] A. Prepare the raw materials for forming the performance enhancement layer, denoted as material A.
[0098] Material A comprises the following raw materials by weight:
[0099] 100 kg of polyamide resin (PA6), particle size ≤ 0.24 mm;
[0100] 25 kg of glass fiber treated with (Titanium ester coupling agent KR-38S), wherein the glass fiber is 3 mm long chopped glass fiber.
[0101] Colorant (lithopone) 0.2kg;
[0102] Lubricant (dimethyl silicone oil) 0.1 kg.
[0103] A-1) The polyamide resin is obtained by grinding polyamide resin granules.
[0104] The specific grinding operation is as follows: use a 60-mesh sieve to screen out the coarse particles in the polyamide resin granules and grind them. The grinding temperature is -20℃ and the grinding time is 3 hours. Then, use a 60-mesh sieve again to sieve to obtain polyamide resin with a particle size ≤0.24mm, and then package and store it.
[0105] B. Prepare the raw materials for forming the melamine-formaldehyde base layer, denoted as material B.
[0106] Material B comprises the following raw materials by weight:
[0107] 100 kg of base material, wherein the base material comprises melamine resin (number average molecular weight of 657, dry state, moisture content ≤1.8%) and cellulose (coniferous α-lignocellulose) in a weight ratio of 10:2;
[0108] The filler is composed of 10 kg of mica powder and 10 kg of dolomite, with a particle size ≤ 0.13 × 10⁻⁶. -3 mm;
[0109] Antioxidant (Antioxidant 168) 0.05 kg;
[0110] Curing agent (ammoniasulfonic acid amine) 0.07 kg;
[0111] Release agent (magnesium stearate) 0.03 kg.
[0112] B-1) The base material is prepared by first kneading melamine resin and cellulose.
[0113] The specific kneading operation is as follows: melamine resin and cellulose are mixed evenly in a kneader according to the weight ratio. The kneader is set to a temperature of 60°C and the kneading time is 45 minutes. After kneading, the material is placed in hot air at 85°C for even drying. After dehydration and drying, the base material is obtained.
[0114] B-2) The filler material first undergoes the following activation treatment:
[0115] Weigh out the surface modifier (titanium ester coupling agent KR-38S), the amount of which is 0.1 wt% of the filler;
[0116] Using propanol as a solvent, the surface modifier was prepared into a modifier solution with a concentration of 10 wt%.
[0117] Set the temperature of the high-speed mixer to 80℃, place the filler in the high-speed mixer and rotate it at 1000 r / min. At the same time, spray the modifier solution and antioxidant prepared in the previous step onto the filler for 15 minutes and mix evenly.
[0118] B-3) Pre-grinding treatment of material B:
[0119] The specific operation is as follows: put material B into a ball mill and grind for 6 hours. The cylinder speed is 20 r / min. The ball mill jacket must be cooled by cooling water. During the grinding process, the temperature of material B should be kept ≤50℃. The material B is then sieved through a 60-mesh sieve to obtain material B with a particle size ≤0.24mm, and then packaged and stored.
[0120] C. The preparation method of melamine formaldehyde products includes the following steps:
[0121] 1) Material B is preheated. Specifically, material B is placed in a high-frequency (high-frequency) preheater at a preheating temperature of 90°C for 40 seconds.
[0122] 2) Prepare and mix the material A. The mixed material A is molded in the female mold and the first male mold of the two-color molding machine. The melamine formaldehyde product per unit area contains 40wt% material A. The mold temperature is 225℃, the molding pressure is 20MPa, the molding time is 50s, and there is one venting in the middle, with a venting time of 1s.
[0123] After molding, the mold temperature is reduced to ≤180℃ to obtain the performance enhancement layer;
[0124] 3) Open the first male mold, and stack material B on the upper surface of the formed performance enhancement layer. The melamine formaldehyde product per unit area contains 60wt% of the material B. Combine the second male mold for compression molding. The mold temperature is 170℃, the compression pressure is 30MPa, the compression time is 40s, and the venting is done once in the middle for 2s.
[0125] After molding, a composite melamine-formaldehyde base layer and a performance-enhancing layer are formed. The mold is cooled to ≤140℃, demolded, trimmed, and polished to obtain melamine-formaldehyde products.
[0126] like Figure 1 As shown, the melamine product prepared in this embodiment has a melamine-formaldehyde base layer 2, and a performance enhancement layer 1 is provided on one side of the melamine-formaldehyde base layer 2.
[0127] Example 3
[0128] Prepare raw materials
[0129] A. Prepare the raw materials for forming the performance enhancement layer, denoted as material A.
[0130] Material A comprises the following raw materials by weight:
[0131] The polyamide resin is composed of 80 kg of PA6 and 20 kg of PA66, with a particle size ≤ 0.24 mm;
[0132] 30 kg of glass fiber treated with (silane coupling agent KH550), wherein the glass fiber is short chopped glass fiber with a length of 5 mm;
[0133] Colorant (rutile type R titanium dioxide) 0.1 kg;
[0134] Lubricant (zinc stearate) 1.5kg.
[0135] A-1) The polyamide resin is obtained by grinding polyamide resin granules.
[0136] The specific grinding operation is as follows: use a 60-mesh sieve to screen out the coarse particles in the polyamide resin granules and grind them. The grinding temperature is -30℃ and the grinding time is 4 hours. After sieving through a 60-mesh sieve, polyamide resin with a particle size ≤0.24mm is obtained, and then packaged and stored.
[0137] B. Prepare the raw materials for forming the melamine-formaldehyde base layer, denoted as material B.
[0138] Material B comprises the following raw materials by weight:
[0139] 100 kg of base material, wherein the base material comprises melamine resin (number average molecular weight of 421, dry state, moisture content ≤1.5%) and pulp in a weight ratio of 10:3;
[0140] 30 kg of filler (light calcium carbonate, whiteness 93, average particle size 0.010 mm);
[0141] Antioxidant 0.1kg, specifically composed of antioxidant 1010 and antioxidant 168 mixed in a mass ratio of 2:1;
[0142] Curing agent (phthalic anhydride) 0.1 kg;
[0143] Release agent (zinc stearate) 0.1kg.
[0144] B-1) The base material is prepared by first kneading melamine resin and pulp.
[0145] The specific kneading operation is as follows: melamine resin and pulp are mixed evenly in a kneader according to the weight ratio. The kneader is set to a temperature of 60°C and a kneading time of 45 minutes. After kneading, the material is placed in hot air at 85°C for even drying. After dehydration and drying, the base material is obtained.
[0146] B-2) The filler material first undergoes the following activation treatment:
[0147] Weigh out the surface modifier (silane coupling agent KH550), the amount of which is 0.5 wt% of the filler;
[0148] Anhydrous ethanol was used as a solvent to prepare a surface modifier solution with a concentration of 20 wt%.
[0149] Set the temperature of the high-speed mixer to 90℃, place the filler in the high-speed mixer and rotate it at a speed of 1300 r / min. At the same time, spray the modifier solution prepared in the previous step onto the filler and stir for 20 minutes until the mixture is uniform.
[0150] B-3) Pre-grinding treatment of material B:
[0151] The specific operation is as follows: put material B into a ball mill and grind for 8 hours. The cylinder speed is 30 r / min. The ball mill jacket must be cooled by cooling water. During the grinding process, the temperature of material B should be kept ≤50℃. The material B is then sieved through an 80-mesh sieve to obtain material B with a particle size ≤0.19mm, and then packaged and stored.
[0152] C. Prepare the raw materials for forming the photosensitive layer, namely melamine powder with a purity of ≥99%, and designate it as material C.
[0153] D. The preparation method of melamine formaldehyde products includes the following steps:
[0154] 1) Material B is preheated. Specifically, material B is placed in a high-frequency (high-frequency) preheater at a preheating temperature of 100°C for 50 seconds.
[0155] 2) Prepare and mix the material A. The mixed material A is molded in the female mold and the first male mold of the two-color molding press. The melamine formaldehyde product per unit area contains 48wt% material A. The mold temperature is 245℃, the molding pressure is 15MPa, the molding time is 60s, and there is one venting in the middle, with a venting time of 1s.
[0156] After molding, the mold temperature is reduced to ≤190℃ to obtain the performance enhancement layer;
[0157] 3) Open the first male mold, and stack material B on the upper surface of the formed performance enhancement layer. The melamine formaldehyde product per unit area contains 50wt% of the material B. Combine the second male mold for compression molding. The mold temperature is 180℃, the compression pressure is 20MPa, the compression time is 40s, and the venting is done once in the middle for 2s.
[0158] After molding, a preliminary product is obtained, which has a composite performance enhancement layer and a melamine-formaldehyde base layer;
[0159] 4) Open the second male mold and lay material C on the upper surface of the initial product. The melamine formaldehyde product per unit area contains 2wt% material C. Combine the second male mold and perform hot pressing. The hot pressing temperature is 180℃, the hot pressing time is 8s, and the hot pressing pressure is 15MPa.
[0160] The mold is cooled to ≤140℃, demolded, trimmed and polished to obtain melamine formaldehyde products.
[0161] like Figure 2 As shown, the melamine product prepared in this embodiment has a melamine-formaldehyde base layer 2, with a performance enhancement layer 1 on one side and a photosensitive powder layer 3 on the other side.
[0162] Example 4
[0163] Prepare raw materials
[0164] A. Prepare the raw materials for forming the performance enhancement layer, denoted as material A.
[0165] Material A comprises the following raw materials by weight:
[0166] 100 kg of polyamide resin (PA6), particle size ≤ 0.24 mm;
[0167] 35 kg of glass fiber treated with (silane coupling agent KH550), wherein the glass fiber is short chopped glass fiber with a length of 1.5 mm;
[0168] Colorant (carbon black) 0.1 kg;
[0169] Lubricant (magnesium stearate) 2kg.
[0170] A-1) The polyamide resin is obtained by grinding polyamide resin granules.
[0171] The specific grinding operation is as follows: use a 60-mesh sieve to screen out the coarse particles in the polyamide resin granules and grind them. The grinding temperature is -40℃ and the grinding time is 4 hours. After sieving through a 60-mesh sieve, polyamide resin with a particle size ≤0.24mm is obtained, and then packaged and stored.
[0172] B. Prepare the raw materials for forming the melamine-formaldehyde base layer, denoted as material B.
[0173] Material B comprises the following raw materials by weight:
[0174] 100 kg of base material, wherein the base material comprises melamine resin (number average molecular weight of 701, dry state, water content ≤1.8%) and pulp in a weight ratio of 10:4;
[0175] The filler is composed of 25 kg of talc powder and 25 kg of montmorillonite powder, with a particle size ≤ 0.13 × 10⁻⁶. -3 mm;
[0176] Antioxidant (antioxidant 1010) 0.8 kg;
[0177] Curing agent (acetyldiphenylamine) 0.8 kg;
[0178] Release agent (calcium stearate) 0.9 kg.
[0179] B-1) The base material is prepared by first kneading melamine resin and pulp.
[0180] The specific kneading operation is as follows: melamine resin and pulp are mixed evenly in a kneader according to the weight ratio. The kneader is set to a temperature of 60°C and a kneading time of 60 minutes. After kneading, the material is placed in a 90°C hot air chamber for uniform drying. After dehydration and drying, the base material is obtained.
[0181] B-2) The filler material first undergoes the following activation treatment:
[0182] Weigh out the surface modifier (silane coupling agent KH550), the amount of which is 1 wt% of the filler;
[0183] Using propanol as a solvent, the surface modifier was prepared into a modifier solution with a concentration of 30 wt%.
[0184] Set the temperature of the high-speed mixer to 100℃, place the filler in the high-speed mixer and rotate it at a speed of 1500 r / min. At the same time, spray the modifier solution prepared in the previous step onto the filler and stir for 30 minutes until the mixture is uniform.
[0185] B-3) Pre-grinding treatment of material B:
[0186] The specific operation is as follows: put material B into a ball mill and grind it for 12 hours. The cylinder speed is 40 r / min. The ball mill jacket must be cooled by cooling water. During the grinding process, the temperature of material B should be kept ≤50℃. Sieve it through a 100-mesh sieve to obtain material B with a particle size ≤0.16mm, and then package and store it.
[0187] C. Prepare the raw materials for forming the photosensitive layer, namely melamine powder with a purity of ≥99%, and designate it as material C.
[0188] D. Prepare decorative paper to form the decorative layer.
[0189] The decorative decal is prepared by: applying melamine photosensitive powder (average particle size 0.19 × 10⁻⁶) to the powder. -3 Add 60 wt% melamine powder to water at 80°C and stir until homogeneous to prepare a mixture containing 60 wt% melamine powder; apply the mixture to the surface of the decal with a coating thickness of 0.1 mm, and dry to obtain the decorative decal.
[0190] E. The preparation method of melamine formaldehyde products includes the following steps:
[0191] 1) Material B is preheated. Specifically, material B is placed in a high-frequency (high-frequency) preheater at a preheating temperature of 80°C for 60 seconds.
[0192] 2) Prepare and mix the material A. The mixed material A is molded in the female mold and the first male mold of the two-color molding machine. The melamine formaldehyde product per unit area contains 30wt% material A. The mold temperature is 270℃, the molding pressure is 10MPa, the molding time is 50s, and there is one venting in the middle, with a venting time of 1s.
[0193] After molding, the mold temperature is reduced to ≤190℃ to obtain the performance enhancement layer;
[0194] 3) Open the first male mold, and stack material B on the upper surface of the formed performance enhancement layer. The melamine formaldehyde product per unit area contains 69wt% of the material B. Combine the second male mold for compression molding. The mold temperature is 190℃, the compression pressure is 15MPa, the compression time is 50s, and there is one venting in the middle, with a venting time of 2s.
[0195] After molding, a preliminary product is obtained, which has a composite performance enhancement layer and a melamine-formaldehyde base layer;
[0196] 4) Open the second positive mold, and cover the decorative paper and material C on the upper surface of the initial product in sequence. The melamine formaldehyde product per unit area contains 1 wt% of material C. Combine the second positive mold and perform hot pressing. The hot pressing temperature is 160℃, the hot pressing time is 10s, and the hot pressing pressure is 18MPa.
[0197] The mold is cooled to ≤140℃, demolded, trimmed and polished to obtain melamine formaldehyde products.
[0198] like Figure 3 As shown, the melamine product prepared in this embodiment has a melamine-formaldehyde base layer 2, a performance enhancement layer 1 on one side of the melamine-formaldehyde base layer 2, a decorative layer 4 on the other side, and a light powder layer 3 on the outer side of the decorative layer 4.
[0199] Comparative Example 1
[0200] Prepare raw materials
[0201] A. Prepare the following weights of raw materials:
[0202] 100 kg of polyamide resin (PA6), particle size ≤ 0.24 mm;
[0203] Colorant (lithopone) 0.2kg;
[0204] Lubricant (dimethyl silicone oil) 0.1 kg.
[0205] A-1) The polyamide resin is obtained by grinding polyamide resin granules.
[0206] The specific grinding operation is as follows: use a 60-mesh sieve to screen out the coarse particles in the polyamide resin granules and grind them. The grinding temperature is -20℃ and the grinding time is 3 hours. After sieving through a 60-mesh sieve, polyamide resin with a particle size ≤0.24mm is obtained, and then packaged and stored.
[0207] B. The preparation method of this comparative example includes the following steps:
[0208] 1) Prepare and mix the above-mentioned raw materials, and then mold them in the female mold and the second male mold of the two-color molding press. The mold temperature is 225℃, the molding pressure is 15MPa, the molding time is 90s, and the air is vented twice in the middle, with each venting time being 1s.
[0209] 2) After molding, the mold temperature is reduced to ≤70℃, the mold is demolded, and the edges are trimmed and polished to obtain this comparative example.
[0210] Comparative Example 2
[0211] Prepare raw materials
[0212] A. Prepare materials A.
[0213] Material A comprises the following raw materials by weight:
[0214] 100 kg of polyamide resin (PA6), particle size ≤ 0.24 mm;
[0215] 25 kg of glass fiber treated with (Titanium ester coupling agent KR-38S), wherein the glass fiber is 3 mm long chopped glass fiber.
[0216] Colorant (lithopone) 0.2kg;
[0217] Lubricant (dimethyl silicone oil) 0.1 kg.
[0218] A-1) The polyamide resin is obtained by grinding polyamide resin granules.
[0219] The specific grinding operation is as follows: use a 60-mesh sieve to screen out the coarse particles in the polyamide resin granules and grind them. The grinding temperature is -20℃ and the grinding time is 3 hours. After sieving through a 60-mesh sieve, polyamide resin with a particle size ≤0.24mm is obtained, and then packaged and stored.
[0220] B. Prepare materials B.
[0221] Material B comprises the following raw materials by weight:
[0222] 100 kg of base material, wherein the base material comprises melamine resin (number average molecular weight of 657, dry state, moisture content ≤1.8%) and cellulose (coniferous α-lignocellulose) in a weight ratio of 10:2;
[0223] The filler is composed of 10 kg of mica powder and 10 kg of dolomite, with a particle size ≤ 0.13 × 10⁻⁶. -3 mm;
[0224] Antioxidant (Antioxidant 168) 0.05 kg;
[0225] Curing agent (ammoniasulfonic acid amine) 0.07 kg;
[0226] Release agent (magnesium stearate) 0.03 kg.
[0227] B-1) The base material is prepared by first kneading melamine resin and cellulose.
[0228] The specific kneading operation is as follows: melamine resin and cellulose are mixed evenly in a kneader according to the weight ratio. The kneader is set to a temperature of 60°C and the kneading time is 45 minutes. After kneading, the material is placed in hot air at 85°C for even drying. After dehydration and drying, the base material is obtained.
[0229] B-2) The filler material first undergoes the following activation treatment:
[0230] Weigh out the surface modifier (titanium ester coupling agent KR-38S), the amount of which is 0.1 wt% of the filler;
[0231] Using propanol as a solvent, the surface modifier was prepared into a modifier solution with a concentration of 10 wt%.
[0232] Set the temperature of the high-speed mixer to 80℃, place the filler in the high-speed mixer and rotate it at 1000 r / min. At the same time, spray the modifier solution and antioxidant prepared in the previous step onto the filler for 15 minutes and mix evenly.
[0233] B-3) Pre-grinding treatment of material B:
[0234] The specific operation is as follows: put material B into a ball mill and grind for 6 hours. The cylinder speed is 20 r / min. The ball mill jacket must be cooled by cooling water. During the grinding process, the temperature of material B should be kept ≤50℃. The material B is then sieved through a 60-mesh sieve to obtain material B with a particle size ≤0.24mm, and then packaged and stored.
[0235] C. The preparation method of melamine formaldehyde products includes the following steps:
[0236] 1) Mix material A and material B together, and then mold the mixture in the female mold and the second male mold of the two-color molding press. The mold temperature is 170℃, the molding pressure is 15MPa, the molding time is 80s, and the venting is done twice in the middle, with each venting time being 1s.
[0237] After molding, the mold is cooled to ≤140℃, demolded, trimmed and polished to obtain this comparative example.
[0238] Examples 1-4 and Comparative Examples 1-2 were cut into test samples for the following tests:
[0239] (1) The notched impact strength was tested according to GB / T 1043 "Determination of impact properties of simply supported plastic beams";
[0240] (2) The high temperature resistance was tested according to GB / T 1634 "Determination of the Deformation Temperature of Plastics under Load", with a load pressure of 1.8 MPa;
[0241] (3) The migration amount of 2,4,6-triamino-1,3,5-triazine (melamine) was determined according to GB 31604.15-2016 "National Food Safety Standard for Food Contact Materials and Articles" to test for harmful substance residues;
[0242] (4) The formaldehyde migration was determined according to GB 31604.48-2016 "National Food Safety Standard for Food Contact Materials and Products" to test for harmful substance residues.
[0243] The specific test results are shown in the table below.
[0244]
[0245] *ND indicates (not detected).
[0246] From the above test results, we can conclude that:
[0247] The thickness of the finished product obtained in Comparative Example 1 is the same as that in Example 2. The layer structure consists of only a PA layer, but the notched impact strength and heat distortion temperature are both lower than those in Examples 1 to 4. That is, the toughness, high temperature resistance and other properties of Comparative Example 1 are not as good as those in Examples 1 to 4. Therefore, although no harmful substances are released from the PA layer, a single PA layer cannot have good mechanical properties and high temperature resistance. This shows that there is a synergistic effect between the component system design and the composite layer structure design of the present invention, achieving the effect of "1+1>2".
[0248] Compared with Example 2, when all materials in Comparative Example 2 were mixed together and molded, the notched impact strength of the final product was much lower than that of Examples 1-4, and the heat distortion temperature was also lower than that of Examples 1-4. Moreover, the formaldehyde migration and melamine migration were greater than those of Examples 1-4. This indicates that the present invention rationally divides the component system and designs it into a composite layer structure, which can not only reduce the release of harmful substances, but also effectively improve the mechanical properties such as toughness and high temperature resistance of melamine formaldehyde products, effectively extend the service life of melamine formaldehyde products and expand the application range of melamine products.
[0249] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A melamine formaldehyde product, characterized in that: At least one melamine formaldehyde base layer is included, and at least one side of the melamine formaldehyde base layer is provided with a performance improvement layer; The raw material for preparing the performance improvement layer is set as material A, and the material A comprises the following raw materials in parts by weight: 100 parts of polyamide resin and 5 to 35 parts of glass fiber; The raw material for preparing the melamine formaldehyde base layer is set as material B, and the material B comprises the following raw materials in parts by weight: 100 parts of base material, 5-50 parts of filler, 0.01-1 part of antioxidant, 0.01-1 part of curing agent, and 0.01-1 part of release agent; Wherein, the base material comprises pulp, one of plant fibers and melamine resin in a weight ratio of 1 to 4:10; The preparation method of the melamine formaldehyde product comprises the following steps: 1) Material A is prepared and subjected to compression molding, with a mold temperature of 200 to 270° C., a compression pressure of 10 to 30 MPa, a compression time of 40 to 90 seconds, and exhaust once in the middle, with an exhaust time of 1 to 3 seconds; After the molding is completed, the mold temperature is lowered to ≤190°C to obtain a performance improvement layer; 2) Preparing the material B, and preheating the material B before adding it into the mold. The specific operation of preheating is: putting the material B into a high-frequency preheating machine, the preheating temperature is 80-140° C., and the preheating time is 20-60 seconds; Material B is superimposed on at least one side of the performance enhancement layer and compression molded together, with a mold temperature of 150-190°C, a compression pressure of 10-30 MPa, a compression time of 40-90 seconds, and exhaust once in the middle, with an exhaust time of 1-3 seconds; After the molding is completed, a composite melamine formaldehyde base layer and a performance improvement layer are formed, the mold is cooled to ≤140°C, demolded, trimmed and polished to obtain a melamine formaldehyde product.
2. The melamine formaldehyde product according to claim 1, characterized in that: The melamine formaldehyde product contains 50-90 wt % of the material B and 10-50 wt % of the material A per unit area.
3. The melamine formaldehyde product according to claim 1 or 2, characterized in that: The material A further comprises a colorant and a lubricant, wherein the weight portion of the colorant is ≤5 parts, and the weight portion of the lubricant is ≤2 parts; The lubricant is one of zinc stearate, magnesium stearate, ethylene bis stearamide, calcium stearate, dimethyl silicone oil, methyl phenyl silicone oil or a mixture of any proportion of the above; The colorant is one or more of titanium dioxide, lead powder, red iron oxide, yellow iron oxide, carbon black, ultramarine, phthalocyanine blue, aluminum powder and fluorescent whitening agent.
4. The melamine formaldehyde product according to claim 1 or 2, characterized in that: It also includes at least one polishing powder layer, which is the outermost layer on either side of the melamine formaldehyde product; The raw material for preparing the polishing layer is set as material C, and the material C is melamine powder. The melamine formaldehyde product per unit area contains ≤5wt% of material C.
5. The melamine formaldehyde product according to claim 1 or 2, characterized in that: It also includes at least one decorative layer formed of decorative flower paper; The preparation method of the decorative paper is as follows: adding melamine varnish powder into water at 60-100° C. and stirring evenly to prepare a mixed solution containing 40-80wt% of melamine varnish powder; spreading the mixed solution on the surface of the paper with a coating thickness of 0.05-0.2mm, and drying to obtain the decorative paper.
6. The melamine formaldehyde product according to claim 1 or 2, characterized in that: The molecular weight of the melamine resin is 300 to 1000, and the water content is ≤2%; The plant fiber is one of wood fiber, bamboo fiber, hemp fiber, rice straw fiber, and cellulose, or a mixture of any proportion of the above; The cellulose is α-lignocellulose; The filler is one or more of talc, heavy calcium carbonate, light calcium carbonate, kaolin, mica powder, dolomite, barium sulfate, graphene oxide, medical stone powder, silica powder, aluminum oxide, montmorillonite powder, diatomaceous earth, and mineral fiber in any proportion; The antioxidant is one of antioxidant 1010, antioxidant 1076, antioxidant 3114, and antioxidant 168, or a mixture of any proportion of the above; The curing agent is one of phthalic anhydride, methyl hexahydrophthalic anhydride, aminosulfonic acid amine, and acetyl dianiline, or a mixture of any proportion of the above; The release agent is one of zinc stearate, magnesium stearate, ethylene bis stearamide, calcium stearate, dimethyl silicone oil, and methylphenyl silicone oil, or a mixture of any proportion of the above.
7. The melamine formaldehyde product according to claim 6, characterized in that: The filler is an activated filler that has been subjected to the following steps: 1) Weighing a surface modifier, wherein the amount of the surface modifier is 0.1 to 1 wt % of the amount of the filler; 2) Using anhydrous ethanol or propanol as a solvent, the surface modifier is prepared into a modifier solution with a concentration of 10 to 30 wt %; 3) Setting the temperature of the mixing equipment to 80-100° C., placing the filler in the mixing equipment and rotating and stirring, and spraying the modifier solution prepared in the previous step onto the filler to mix evenly.
8. The melamine formaldehyde product according to claim 1 or 2, characterized in that: The polyamide resin is one of PA6 and PA66 or a mixture of the two in any proportion, with a particle size of ≤0.28mm; The glass fiber is chopped glass fiber with a length of 1.5 to 15 mm; The glass fiber is a glass fiber modified by a coupling agent, and the coupling agent is one of a silane coupling agent, an aluminate coupling agent, and a titanate coupling agent, or a mixture of more than one of the above in any proportion.
9. The melamine formaldehyde product according to claim 1, characterized in that: After the molding is completed in step 2), material C that can form a glossy powder layer and / or decorative flower paper are laid on at least one side of the melamine formaldehyde base layer and / or the performance enhancement layer, and hot pressing is performed at a temperature of 150 to 190° C., a time of 5 to 10 seconds, and a pressure of 12 to 18 MPa.
Citation Information
Patent Citations
Antibacterial and wear resistant melamine ware and preparation method thereof
CN106883553A
High-toughness melamine resin and preparing method thereof
CN106700415A
Mould pressing preparation method of melamine material for light tableware
CN116855036A